1992
DOI: 10.1088/0953-4075/25/15/002
|View full text |Cite
|
Sign up to set email alerts
|

Search for the spectrally narrow radiative decay of 2p34So3/2in He-

Abstract: Radiative autoionization (RA) of the 2p3 4So state in the He- ion has been predicted to result in a narrow spectral feature near lambda =32.315 nm. The authors have observed a weak, line-like structure at lambda =(32.32+or-0.02) nm, in spectra of foil-excited He ions at incident energies in the range 140-200 keV. This would be the first observation of this elusive RA process. The measurements and supportive evidence are presented as well as preliminary results for electronically similar ions of B and C, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…However, to provide an example, the author chose here the He Ϫ 1s2p 2 4 P state, which is a core-excited shape resonance with a lifetime of 1 ϫ 10 Ϫ13 s, lying about 11meV above the He 1s2p 3 P 0 threshold [11][12][13]. There are at least three processes for the formation of this state: (1) laser-induced photoexcitation of the metastable 1s2s2p 4 P 0 state [12,13], (2) radiative decay of the He Ϫ 2p 3 4 S 0 excited bound state [13,14], and (3) electron scattering eϪ ϩ He 1s2p 3 P 0 (not done yet).…”
Section: Introductionmentioning
confidence: 99%
“…However, to provide an example, the author chose here the He Ϫ 1s2p 2 4 P state, which is a core-excited shape resonance with a lifetime of 1 ϫ 10 Ϫ13 s, lying about 11meV above the He 1s2p 3 P 0 threshold [11][12][13]. There are at least three processes for the formation of this state: (1) laser-induced photoexcitation of the metastable 1s2s2p 4 P 0 state [12,13], (2) radiative decay of the He Ϫ 2p 3 4 S 0 excited bound state [13,14], and (3) electron scattering eϪ ϩ He 1s2p 3 P 0 (not done yet).…”
Section: Introductionmentioning
confidence: 99%
“…The 1s2p2p' P' shape resonance has been measured in such a way by Peterson, Coggiola, and Bae [5]. Very recently Trabert et al [16] have observed this resonance in emission from the 2p S' metastable state. The latter work was preceded by theoretical prediction of Nicolaides and Komninos [6] and Nicolaides [17], and is the first experimental confirmation of the 2p S' state as first predicted by Beck and Nicolaides [18].…”
Section: B Generalized Saddle-point Methodsmentioning
confidence: 99%
“…Its energy is known from theory as being around 59.33 eV above the ground state [3,4] and, in fact, it was recently identified experimentally [5] from the predicted characteristic property of its radiative decay to the He 1s 2p P '+ e continuum [3,4].…”
Section: Known N =2 Triply Excited States Of Hementioning
confidence: 99%
“…For @McHF(1), the energy shift is small and positive whereas for @McHF (1) it is large and negative. As regards the results on the widths from expressions (5) and (6), the following facts should be noted. The final state did not include core correlation.…”
Section: Localization Interpretation Of the Mchf Solutions And mentioning
confidence: 99%